Hubungan Pengetahuan Perawat Dengan Pelaksanaan Bantuan Hidup Dasar (BHD) di IGD RS Mitra Sejati Medan Tahun 2022 - Elny Lorensi Silalahi; Wiwik Dwi Arianti; Ida Suryani Hasibuan (Barongko: Jurnal Ilmu Kesehatan, 2022)
Basic life support or basic life support (BLS) is the first attempt made to maintain life when the patient experiences a threatening situation. Emergency events are unpredictable and can happen anywhere and to anyone. Delays and errors in handling them can have very fatal and irreparable effects in subsequent actions. The purpose of this study was to find similarities, advantages, and disadvantages regarding the description of the knowledge and implementation of basic inhalation assistance (BHD) for emergency nurses in emergency departments. This research method uses a correlational descriptive method. The large number of samples in this study uses a minimum sample of 38 respondents with inclusion and exclusion criteria. Data analysis based on percentage and described in the frequency distribution table. The results of the study show that there is a relationship between knowledge and skills of nurses in carrying out basic life support measures in the emergency department of Mitra Sejati Hospital in Medan. The level of relationship between the two variables is (+/positive) 0.458, which means that the strength of the relationship is at a moderate level of relationship. In addition, this positive relationship means an increase in knowledge followed by an increase in the skills of nurses in carrying out basic life support measures.